Public policies in Brazil: An analysis of prenatal care and prematurity - Rocha, Marcone Marques da; Barbosa, Roberta Ribeiro Batista; Oliveira, Fernando Rocha (Seven Editora, 2023)
This scientific article presents an analysis of public policies in Brazil related to prenatal care and prematurity. The study seeks to understand the government's approach to prenatal care offered to pregnant women and the impact of these policies on the incidence of premature births in the country. For this, a literature review was carried out, examining scientific studies and official documents that address the subject. The analysis revealed that prenatal care in Brazil is offered free of charge by the Unified Health System (SUS) and aims to monitor pregnancy and identify possible complications early. However, despite efforts to improve access to and quality of prenatal care, there are still challenges to be faced, such as the need to improve the training of health professionals and the infrastructure of care units. Public policies for early intervention aim to minimize the impacts of prematurity, with actions that include adequate respiratory support, the promotion of breastfeeding, the prevention and treatment of infections, among other measures. Given the challenges identified, the study concludes that it is essential to improve public policies in Brazil for prenatal care and prematurity. Investments in training of health professionals, preventive actions and adequate support for pregnant women can contribute to reducing the incidence of premature births and improving the quality of life of babies and their families. In addition, the awareness of society about the importance of prenatal care and adequate care for premature babies is essential for the promotion of a more effective and comprehensive maternal and child health in the country. DOI:https://doi.org/10.56238/innovhealthknow-032